SASSI and the MSC: How effective have they been with reaching consumers in Cape Town and raising their awareness - Landey, David (Department of Oceanography, 2014)
The 'sustainable seafood movement' is over 20 years old, and has made use of numerous methods in an attempt to educate consumers about seafood. In South Africa, there are two such campaigns: the Marine Stewardship Council (MSC) and the Southern African Sustainable Seafood Initiative (SASSI). This study aimed to investigate the awareness of consumers at major retail outlets in Cape Town of these initiatives, and to link awareness with seafood consumption behaviour. It used face-to-face surveys, which were conducted at all times of the week in outlets of three major supermarket chains located at five middle-class shopping centres. Aspects investigated included consumers': recognition of the MSC and SASSI; preferred seafood species; production method(s); and favoured sources of seafood. The data were analysed by means of chi-squared (χ2) analysis. The MSC label was recognised by slightly over a tenth of the consumers and SASSI by just less than half. Overall it was found that shoppers were more concerned about the quality and value for money, than the type, sustainability and size of their seafood. Consumers who shopped at the retail outlets which have a working relationship with SASSI did not show a higher awareness of SASSI. Even the consumers who were the most aware of SASSI and/or the MSC, and indicated that they considered sustainability a factor when making seafood choices, still favoured species from fisheries the sustainability of which is classified as problematic. The results point to raised awareness, yet unchanged purchasing behaviour.